Ground Vibration Engineering Simplified Analyses with Case Studies and Examples - Srbulov, Milutin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Ground vibration consideration is gaining significance with people$1 (Bs decreasing tolerance of vibration, introduction of new environmental legislations, increasing use of equipment sensitive to vibration, ageing of existing buildings and expanding construction sites to/near collapsible/liquefiable/thixotropic soil. This volume bridges the gap that exists between rather limited provisions of engineering codes/standards and complex numerical analyses/small-scale tests. The book contains descriptions of ground vibration measurements, predictions and control for engineers. Effects of most frequent sources of ground vibration arising from construction/demolition, traffic and machinery, ground wave amplification and attenuation as well as foundation kinematic and inertial interaction have been considered by simplified analyses aimed at ease and speed of use for major problems in ground vibration engineering. Comments on assumptions, limitations, and factors affecting the results are given. Case studies and examples worldwide are included to illustrate the accuracy and usefulness of simplified methods. A list of references is provided for further consideration, if desired. Audience: This work is of interest to geotechnical engineers, engineering geologists, earthquake engineers and students. Extra material: Microsoft Excel spreadsheets with the input data and results for the case studies and examples considered in this book are available at http://extras.springer.coms
Problem Description -- Ground Waves Propagation -- Ground Vibration Measurement -- Processing of Vibration Records -- Foundation and Structure Effects -- Ground Investigation for Vibration Prediction -- Prediction of Vibration Amplitudes -- Control of Ground and Foundation Vibration -- Effects on Soil Slopes and Shallow Foundations.
Keywords: Geography; Hydraulic engineering; Ecology; Earth Sciences; Geotechnical Engineering & Applied Earth Sciences; Geoengineering, Foundations, Hydraulics; Building Construction; Geotechnical Engineering & Applied Earth Sciences; Geoecology/Natural Processes